THE EVALUATION OF THE AL-QUR'AN SANAD PROGRAM AT THE TAHFIZH TILAWAH AL-QUR'AN SCIENCE INSTITUTEAT PONDOK PESANTREN AL-ITTIFAQIAH INDRALYA, OGAN ILIR REGENCY - Pebriyanti Pebriyanti; Firdaus Basuni; Muyasaroh Muyasaroh; Zaimmuddin Zaimmuddin (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to describe the evaluation of the Qur'an tahfizh sanad program at the Al-Ittifaqiah Qur'an Science Tahfizh Tilawah Institute, which will be studied using qualitative research methods with an evaluative approach. Data collection techniques in this study were interviews and observations. The data were analyzed using the Milles and Huberman model with the stages of data reduction, data presentation, and data withdrawal or conclusions to determine the validity of the data using source triangulation. The results of this study found that in terms of input evaluation, students' initial ability must be khatam AL-Qur'an without any Qur'an memorization selection test. Evaluation of the process of the method has met the standards, the teacher who teaches actively so that the implementation is effective. Then in terms of product evaluation, Of the 58 students who participated in the Qur'an tahfizh sanad program, only 3 passed. Compared to the total number of students, this number needs improvement, only approximately 5%.